Health Economics: An Industrial Organization Perspective - Supakankunti, Siripen (Asian Journal of Applied Economics, 2013)
“This book covers the economic theories, mathematical models, and analytical casesin the health services market. Most of the cases are from developed countries. Whilethese can be instructive to workers in developing economies, their relevance andapplications in developing countries are limited.”